FEATURES OF THE USE OF LASER TECHNOLOGIES IN THE SURGICAL TREATMENT OF ENDOMETRIAL POLYPS - Rymashevsky , Alexander Nikolaevich; Drobin , Oleg Yuryevich (Mother and Baby in Kuzbass, 2026)
Objective – to evaluate the results of surgical treatment of endometrial polyps using various methods of intrauterine use of laser technologies. Materials and Methods. An applied single-center comparative non-randomized prospective study that included patients who underwent intrauterine surgical treatment of endometrial polyps. At the gynecological department of the State Budgetary Institution RO CDC «Health» in Rostov-on-Don, 90 patients aged from 19 to 78 years were examined. Group I – 45 patients who had endometrial polyps removed using a holmium laser; Group II – 45 patients who had endometrial polyps removed using a thulium laser. The relapse rate was studied using ultrasound examination at 3, 6 and 12 months after surgical treatment. Results. According to ultrasound examination data, recurrent endometrial polyps were detected in 4 (8.9%) patients in Group I. In Group II, recurrent polyps were detected in 2 (5%) cases. Intrauterine adhesions were detected in 3 (6.7%) patients in Group I and 1 (2.2%) in Group II. This observation may indirectly indicate a higher invasiveness of the holmium laser in the surgical treatment of endometrial polyps compared to the thulium laser. Conclusions. Laser technologies have firmly entered the arsenal of modern medicine; their potential in gynecological practice has not yet been fully revealed. Our studies have revealed that the use of laser methods can not only significantly reduce the risk of recurrence of endometrial polyps in patients of different ages, but also prevent the formation of postoperative synechiae in the uterine cavity.